Telescope الضوء الهندسي و التقريب الفلكي تجسيد مقراب - طريلي, شفاء; قسط, لبنى (Université of eloued جامعة الوادي, 2025)
يعد علم البصريات من أهم فروع الفيز ياء التي ساهمت في تقدم العلوم وخاصة في مجال استكشاف الفضاء.وقد مكنت المقاريب البصرية العلماء من دراسة الأجرام السماو ية بدقة عالية وهو ما أدى إلى تحقيق اكتشافات فلكية عظيمة. وفي هذه المذكرة تم التعرف على أنواع هذه المقاريب ومكوناتها ومبدأ عملها بالإضافة إلى مزايا وعيوب كل نوع واستخداماتها.ومن بين أبرز أنواع المقاريب يبرز مقراب نيوتن العاكس الذي تم تجسيده عمليا بًإستخدام أدوات بسيطة متمثلة في مرآة مقعرة وأخرى مسطحة مائلة بهدف توضيح كيفية عمله وتعزيز الفهم التطبيقي للمفاهيم البصرية وتوضيح فائدته في تكبير صور الأجسام البعيدة، مما يجعل من هذا البحث جسرا بًين النظر ية والتجريب في علوم الضوء والفلك. ،Optics is one of the most important branches of physics that has contributed to the advancement of science, especially in the field of space exploration.Optical telescopes have enabled scientists to study celestial objects with high precision, leading to great astronomical discoveries. This note identifies the types of these telescopes, their components, and operating principles, in addition to the advantages and disadvantages of each type and their uses.Among the most prominent types of telescopes Newton’s reflecting telescope stands out.It was embodied practically using simple tools,consisting of a concave mirror and a flat,inclined mirror,with the aim of clarifying how it works,enhancing practical understanding of optical concepts,and demonstrating its usefulness in magnifying images of distant objects.This makes this research a bridge between theory and experimentation in the sciences of light and astronomy.
فيزياء تطبيقية إشعاع وطاقة
Keywords: علم البصريات، الضوء الهندسي، المرايا، العدسات، الانعكاس، الانكسار; المقاريب البصرية، مقراب نيوتن العاكس.; Optics; Geometric light; Mirrors; Lenses; Reflection; Refraction; Optical telescopes; Newton’s reflecting telescope.